2016
DOI: 10.3402/fnr.v60.30045
|View full text |Cite
|
Sign up to set email alerts
|

Body mass but not vitamin D status is associated with bone mineral content and density in young school children in northern Sweden

Abstract: BackgroundHigh latitude of residence where sun exposure is limited affects vitamin D status. Although vitamin D levels have been associated with poor bone health, cut-off values for optimising bone health are yet to be decided.ObjectiveTo assess vitamin D intake and status among young school children living at latitude 63–64 °N, in northern Sweden and to examine the association between vitamin D status and bone mineral content (BMC) and bone mineral density (BMD).DesignIn a cross-sectional study, diet was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
5
5
0
2
Order By: Relevance
“…The main finding of this study was that age and BMI affect BMD and BMC in a diverse group of 4-to-6 year old children but not serum 25(OH)D concentration; however, 25(OH)D concentration was shown to be associated with percent body fat. These BMC and BMD outcomes are consistent with a study of 8-to-9 year old children in Sweden [13]. Also, this latter result complements a study that reported obesity and serum 25(OH)D concentrations are inversely related [14].…”
Section: Discussionsupporting
confidence: 90%
“…The main finding of this study was that age and BMI affect BMD and BMC in a diverse group of 4-to-6 year old children but not serum 25(OH)D concentration; however, 25(OH)D concentration was shown to be associated with percent body fat. These BMC and BMD outcomes are consistent with a study of 8-to-9 year old children in Sweden [13]. Also, this latter result complements a study that reported obesity and serum 25(OH)D concentrations are inversely related [14].…”
Section: Discussionsupporting
confidence: 90%
“…òàçîãðåáíåâîé øèðèíîé ó äåòåé â ïðîöåññå ðîñòà; äðóãèå ïðîïîðöèè îáÿçàíû â ñâîåé âàðèàöèè áîëüøåé ÷àñòüþ ôàêòîðó ïèòàíèÿ è îñíîâîïîëàãàþùèì ìåõàíèçìàì ðîñòà [Cowgill et al, 2012] Îòðèöàòåëüíîå âëèÿíèå õîëîäîâîãî ñòðåññà íà äëèíó òåëà îòìå÷åíî òàêaeå äëÿ ìåêñèêàíñêèõ äåòåé â âîçðàñòå 12-47 ìåñÿöåâ â öåíòðàëüíûõ è þaeíûõ ÷àñòÿõ ñòðàíû è âûñîêîãîðíûõ ðåãèîíàõ [Skoufias, Vinha, 2012]. Ïî ðåçóëüòàòàì ðåãðåññèîííîãî àíàëèçà êëèìàòè÷åñêèå ïåðåìåííûå (ñðåäíåãîäîâîé óðîâåíü îñàäêîâ, ñðåäíåãîäîâàÿ òåìïåðàòóðà íà ìîìåíò ãåñòàöèè, ðîäîâ è â âîçðàñòå äåòåé 2-4 ãîäà), íå ñâÿçàíû ñ âàðèàöèÿìè äëèíû òåëà ìîëîäûõ aeåíùèíà è ìóae÷èí (âïëîòü äî 23 ëåò), êîðåííûõ aeèòåëåé Àìàçîíèè, (Áîëèâèÿ), íî òåì íå ìåíåå âíîñÿò âêëàä â èçìåí÷èâîñòü äëèíû òåëà äåòåé 2-12 ëåò: ñ óâåëè÷åíèåì òåìïåðàòóðû è âëàaeíîñòè äëèíà òåëà âûøå [Godov et al, 2008 [Nikooyeh et al, 2017, Videhult et al, 2016. Àññîöèàöèÿ ñîìàòè÷åñêèõ ïîêàçàòåëåé è îí-êîëîãè÷åñêîé çàáîëåâàåìîñòè -òåìà äëÿ îòäåëüíîé áåñåäû, íî êîíñïåêòèâíî ìîaeíî óïîìÿíóòü, ÷òî êðèâàÿ ïîëîâîçðàñòíûõ ïîêàçàòåëåé ÷àñòîòû îíêîëîãè÷åñêèõ çàáîëåâàíèé õàðàêòåðèçóåòñÿ ïèêîì â âîçðàñòíîé ãðóïïå 1-4 ãîäà, ñïàäîì -ó äåòåé 5-10 ëåò è ïîâòîðíûì ïîäúåìîì ñ 11-12 ëåò; à â ÷èñëå èíôîðìàòèâíûõ ñèìïòîìîâ/ñèíäðîìîâ îíêîëîãèè ïðèñóòñòâóåò è ñíèaeåíèå ìàññû òåëà [Áàðüÿø ñ ñîàâò., 2013;Âåðíåð, Êåéðî, 2008;Principles..., 2012].…”
Section: Discussionunclassified
“…Epidemiological studies have evaluated the correlation between the circulating 25(OH)D level and the BMD value, but the results were controversial. Some studies have reported a positive association between the serum 25(OH)D level and the BMD at the hip and spine (Saquib et al, 2006, von Muhlen et al, 2005), while others found no such association (Videhult et al, 2016, Sayed-Hassan et al, 2016, Garnero et al, 2007). The associations between the total 25(OH)D level and the biomarkers of bone turnover were also suggested to be affected by the sex, age, disease status and medication use of the study participants (Garnero et al, 2007, Lu et al, 2012, Hernandez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%